In search of modern humans and the Early Upper Paleolithic at Manot Cave: An overview. Issue 160 (November 2021) - Barzilai, Omry; Marder, Ofer; Hershkovitz, Israel
Abstract: Manot Cave is a unique relict karst cave located in the western Galilee, north-western Israel. The cave was inhabited from the Late Middle Paleolithic through the Early Upper Paleolithic (EUP) periods until its main entrance collapsed, ca. 30 ka. The cave consists of an elongated main hall and two side chambers. The topography of the main hall consists of a steep talus inclining from the original entrance of the cave to the center, a plane area at the lowermost point of the main hall, and a smaller talus inclining from the eastern end of the cave. Nine field seasons (2010–2018) have been conducted so far at the cave. The excavations revealed dense accumulations of EUP deposits near the cave entrance (areas E and I), at the center (area D), at the base of the western talus (area C), and in the plane area (area A). This introductory article describes the cave and its characteristics and provides a background for various contributions in the special issue, devoted to Manot Cave.